Lokakarya Berani Bicara dan Pandai Mendengar: Efektivitas Experiential Learning dalam Meningkatkan Kemampuan Komunikasi Siswa SD - Jahja Widjaja; Fanny Kristine; Imelda Junita; Kezia Kurniawati Nursalin; Meily Margaretha; Rully Arlan Tjahyadi; Susanti Ridawaty Saragih; Sherlywati (Jurnal Atma Inovasia, 2026)
This article presents a report on a community service program in the form of a Public Speaking workshop “Dare to Speak and Good at Listening” for students in grades 1, 2, and 3 of Bandung Baptist Elementary School. This program was designed in response to the results of a Focus Group Discussion with parents and teachers that identified gaps in children’s communication skills, particularly speaking courage and listening skills. The method used was an experiential learning approach through a one-day interactive workshop on October 10, 2025, involving 47 students. Effectiveness was measured by pre-test and post-test observation sheets on 5 selected students and verbatim documentation of all activities that included eight stages, from ice breaking to reflection. The analysis results showed an increase in observation scores from 82 to 94 (+12 points). The most significant improvements were recorded in the aspects of public speaking courage and active listening skills, while technical aspects such as eye contact and voice clarity still require ongoing practice. Qualitative data confirmed the transformation of student behavior through more active participation and the application of communication ethics. This program has proven effective as an early intervention that bridges children’s communication gaps. Recommendations include the integration of experiential learning into the curriculum of subsequent workshops, as well as active parental involvement for sustainability.